2012
DOI: 10.5935/1678-9741.20120106
|View full text |Cite
|
Sign up to set email alerts
|

Off-pump versus on-pump coronary artery bypass surgery: meta-analysis and meta-regression of 13,524 patients from randomized trials

Abstract: Off-pump versus on-pump coronary artery bypass surgery: meta-analysis and meta-regression of 13,524 patients from randomized trials Abstract Background: Most recent published meta-analysis of randomized controlled trials (RCTs) showed that off-pump coronary artery bypass graft surgery (CABG) reduces incidence of stroke by 30% compared with on-pump CABG, but showed no difference in other outcomes. New RCTs were published, indicating need of new meta-analysis to investigate pooled results adding these further st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 48 publications
1
18
0
Order By: Relevance
“…Two other prior meta-analyses (33,34 ) also evaluated the use of off-pump CABG in cardiovascular surgery, but in contrast to our study, they did not limit their analysis to patients who were ≥70 years of age. The meta-analysis of Sa et al (34) included 47 RCTs with 13,524 patients (6,758 for off-pump and 6,766 for on-pump CABG).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two other prior meta-analyses (33,34 ) also evaluated the use of off-pump CABG in cardiovascular surgery, but in contrast to our study, they did not limit their analysis to patients who were ≥70 years of age. The meta-analysis of Sa et al (34) included 47 RCTs with 13,524 patients (6,758 for off-pump and 6,766 for on-pump CABG).…”
Section: Discussionmentioning
confidence: 99%
“…The meta-analysis of Sa et al (34) included 47 RCTs with 13,524 patients (6,758 for off-pump and 6,766 for on-pump CABG). They found no difference between treatments in 30-day mortality or myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of randomized trials comparing on-pump to off-pump coronary artery bypass grafting surgery demonstrated a 20.7% reduction in stroke incidence in off-pump patients (35). However, a Cochrane review of 86 randomized trials did not show a difference in stroke rates when comparing on-pump to off-pump patients (36).…”
Section: Discussionmentioning
confidence: 99%
“…Current best available evidence in the form of metaanalyses and systematic reviews of RCTs as well as propensity score matched studies confirms comparable impact of off and onpump CABG on short, mid, and longterm mortality as well as major cardio and cerebrovascular events with fewer distal anastomoses, poor SVG patency, and increased repeat revascularization rates after offpump CABG. [18][19][20][21][22][23][24][25] Since its renaissance nearly 2 decades ago, offpump CABG has remained a subject of intense scrutiny. It has been compared with the gold standard onpump CABG in numerous RCTs as well as large retrospective observational studies.…”
Section: Discussionmentioning
confidence: 99%